The leadership behavior of the physical education and sports teacher and its relationship to the level of creative thinking among secondary school students - bachiri, benattia (sports creativity, 2025)
This study aims to identify the distinctive leadership behavior of physical education teachers and the level of creative thinking among secondary school students, and to explore the relationship between them. The researcher posed the following questions: 1. What is the distinctive leadership behavior of physical education teachers? 2. What is the level of creative thinking among secondary school students? 3. Is there a correlation between the dominant leadership behavior of physical education teachers and the level of creative thinking among secondary school students? The results indicated that social leadership behavior is the most frequently used and prevalent among physical education teachers, while dictatorial behavior was the least common. The results also showed a correlation between dominant leadership behavior and the level of creative thinking among students. Furthermore, the results indicated a strong positive correlation between social leadership behavior (considered dominant) and the level of creative thinking among students. Finally, the results showed an inverse correlation between dictatorial leadership behavior and the level of creative thinking among secondary school students.